Edukasi Berbasis Lingkungan sebagai upaya Meningkatkan Kepedulian Masyarakat di Bantaran Kali Acai Abepura - Sapioper, Hiskia CM.; Modouw, James; Ramandei, Lazarus; Rorrong, Semuel D. (Neolectura, 2024)
Community Service Activities regarding environmental-based education, as an effort to increase community awareness of the quality of the environment, but also a form of concern for the service team from Cenderawasih University towards environmental problems which are increasingly less controlled along the Acai River. Through environment-based education, we can form souls who have high environmental awareness. Starting from the lower and middle classes of society, it is hoped that they will become agents of change. Through outreach activities and using environmental campaign media through songs and calls for environmental safety, it is hoped that it can inspire the community so that the community can become an agent of change for the environment in the future. This Community Service activity aims to shape the mindset and concern of the community in promoting environmental care movements to create clean, comfortable and healthy conditions starting from providing education on the importance of keeping the environment clean, recognizing and classifying the types of waste in the area, how to use waste, planting plants in one's own environment, and environmental campaigns through songs and calls for the safety of the environment and the earth. Environmental cleanliness must come from the family environment so that it forms a far-sighted mindset and will become an agent of change in their environment through healthy lifestyle education programs.